THE COMMUNITY PROTECTION ON DISASTER MITIGATION PERSPECTIVE OF LOCAL GOVERNMENT LAW: AN EMPIRICAL STUDY - Joko Pramono; Dora Kusumastuti (Universitas Slamet Riyadi, 2021)
According to mandate Act Number 23 the year 2014 on regional government that local governments had one obligation of community protection division for service. The role of community protection one of them is disaster mitigation. The objective that performs the functions of research is to know and how local government efforts in carrying out on obligatory basic service of disaster mitigation by community protection with the increasing number of cases disasters is empirical research in Indonesia. Method of juridical because use primary data obtained by interviews, FGD, and observation. Data analyzed to use the technique can draw interactive analysis to concluding. The local government efforts in carrying out on obligatory basic service disaster mitigation command regions conducted of disaster training, members always involved in the disaster, and always coordinate with an agency that has authority main of disaster perform the functions.Not ideally of percentage members and several people as well as the limited need to follow-up facilities from local government to realize community protection division for basic service.